Efeito do diminazeno, um ativador da ECA-2, no remodelamento cardíaco de ratos submetidos ao infarto do miocárdio - Castardeli, Carmen (2016)
Diminazene aceturate (DIZE) is used with an antitrypanosomal action for veterinary use which is also able to increase the catalytic efficiency of ACE-2. Thus the objective of our work was to investigate the effects of DIZE on the postinfarction cardiac remodeling process. Besides that, data with DIZE treatment were compared to those obtained in the same experimental model submitted to Losartan (Los). Rats Male Wistar were submitted to a surgical procedure to produce permanent occlusion of the left coronary artery to produce MI, the control animals underwent the same surgical procedure but without arterial occlusion. After surgery the animals were divided into five groups: (1) Control Rats + Placebo (Pla-Con, n = 8); (2) Controls Rats + DIZE (Con-DIZE; n = 6); (3) Infarcted Rats + Placebo (Pla-IM, n = 7); (4) Infarcted Rats + DIZE (IM-SAY; n = 6); (5) Infarcted Rats + Losartan (MI-Los; n = 7) were administered daily subcutaneous injection of 15 mg / kg (DIZE and / or LOS) and Placebo (0.9% NaCl) for 28 days. After 28 days the animals were anesthetized to record the intracardiac hemodynamic variables. After recording hemodynamic variables, the cardiac beats were stopped diastole with an intravenous injection of KCl (1 M). A double lumen catheter was inserted into the left ventricular cavity to obtain the record of the pressurevolume curve. Hearts were fixed in formalin and processed to histological analysis of myocyte hypertrophy and collagen content. The group IM-Pla presented a significant increase in the left ventricular end diastolic pressure (LVEDP = 26±3,3 mmHg) and also a significant reduction of +dP/dt (3014 ± 161 mmHg/s), -dP/dt ( -2333±91 mmHg/s) and systolic blood pressure (SBP = 101±3 mmHg), as compared with the groups treated with DIZE (LVEDP = 15±1,6 mmHg/s; +dP/dt 3884±104 mmHg/s; -dPdt = -2798±120 mmHg/s and SVE = 110±0,7 mmHg) or Los (LVEDP = 16±2,9 mmHg; +dP/dt: 4146±131 mmHg/s; -dPdt = -2823±136 mmHg/s; SBP = 111±3,5 mmHg). The right ventricle hemodynamic revealed an increase in systolic pressure in the IM-Pla group (40±0,6 mmHg) with a small decrease in the IM group under DIZE (37±2 mmHg). The IM-DIZE (0,33±0,03 mmHg/mL e 0,64±0,01 mmHg/mL) and IM-Los (0,36±0,03 mmHg/mL e 0,65±0,04 mmHg/mL) groups showed less left ventricular dilatation and stiffness as compared with the infarcted group under Pla (0,39±0,03 mmHg/mL e 0,78±0,02 mmHg/mL). The volumetric fraction of collagen in the surviving left ventricular myocardium increased, was partially prevented by DIZE or Los treatment. The postinfarction hypertrophy of cardiomyocytes, however, remained unaffected by DIZE treatment. As expected, treatment with losartan attenuated the hypertrophic growth in the left ventricle. In conclusion, our study showed that DIZE was effective to partially prevent the hemodynamic changes induced by infarction in rats similarly to the observation in infracted rats treated with Los. The two drugs also prevented the increase in the collagen deposition in the surviving left ventricular myocardium. In relation to the hypertrophic of cardiomyocytes, however, only Los showed a preventive effect.